Soils of Misiones - Moretti, Lucas Martin (2019)
The Province of Misiones in northeastern Argentina is characterized by the dominance of red soils, developed under a subtropical climate and rainforest vegetation cover. These soils were developed from the weathering of the tholeiitic basalts that outcrops in some parts of the region. Based on the soil–landscape relationship, the following units can be differentiated: 1) the “Preserved Central Plateau,” constitutes the watershed of the Paraná and Uruguay basins, where deep Ultisols and Oxisols are present. 2) The “Partially Dissected Peniplain,” along the valley of Paraná and Iguazú rivers has deep soil profiles (mainly Alfisols and Ultisols). 3) The “Partially Dissected Peniplain without Arboreal Vegetation,” is formed by dome-shaped hills where Alfisols and Ultisols are common. 4) The “Strongly Dissected Mountain Relief” in the central-east part of the province, present soils poorly developed, classified as Mollisols and Entisols. 5) The “Strongly Undulated Relief” surrounds the previous unit and presents Mollisols and Entisols of moderate development. 6) The “Foothills of the Preserved Plateau” appears insert in the previous one, where Alfisols, Ultisols, and Inceptisols are the dominant orders. 7) The “Secondary Valleys with alluvial deposits” consists of a complex of soils, with aquic moisture regime and vertic features. Local soils are classified as Mollisols and Alfisols. 8) The “Encased and Dissected Areas” are present in the valleys of Paraná and Uruguay rivers, with Mollisols as the dominant soil order. 9) The “Gently Rolling Plains and Rocky Outcrops” located in the northeastern part of the province is characterized by the dominance of Mollisols